Optimization of the documentary management process with a web system based on the Framework EXT JS, for the Regional Government of Tacna, 2017 - Mamani Flores, Blácido Jhony (2019)
The present investigation consists of the optimization of the Document Management Process with a Web System Based on the Ext JS Framework for the Regional Government of Tacna.  The thesis has as purpose improve with a web system based on the EXT JS Framework the document management process, was focused on answering the causes that are studied between the two variables, web system and document management as time of attention of documents, time to generate documentary follow-up report and user satisfaction. The methodology used to obtain the analysis data in the quasi-experimental design. We analyzed a population of 267 users, whose data collected from these were submitted to descriptive statistics and inferential statistics of a simple from 158 users. Obtaining in this way results that allow us to know the present problematic that has the Regional Government of Tacna. It is concluded that the document management process was improved in 31.5%, Reduced the time of attention in 2.2 minutes, the time to generate documentary follow-up report in 62 seconds and Increase user satisfaction in 48.3%.